SHORT TERM NEONATAL OUTCOMES IN PREGNANCY INDUCED HYPERTENSION. (18th May 2018) - Razak, Abdul; Patel, Waseemoddin; Durrani, Naveed; McDonald, Sarah; Shah, Prakeshkumar; Mukerji, Amit
Abstract: BACKGROUND: Studies have demonstrated heterogeneity in association of pregnancy-induced hypertension (PIH) and respiratory outcomes or mortality in preterm infants, largely attributed to effect of gestation and antenatal steroids (survival bias). OBJECTIVES: To comparatively evaluate mortality and short-term respiratory outcomes in preterm infants < 33 weeks GA born to mothers with and without PIH. DESIGN/METHODS: This retrospective cohort study of preterm infants younger than 33 weeks' gestation born between July 1, 2014 to June 30, 2016 was conducted at a tertiary academic hospital. Infants exposed to PIH (exposure) were matched to infants not exposed to PIH (control) in a 1:2 ratio, based on gestation, sex and antenatal steroid exposure status. The primary outcomes were respiratory index (RI), mortality and bronchopulmonary dysplasia (BPD). RI was defined as area under curve (AUC) for mean airway pressure and fraction inspired oxygen on invasive ventilation during first 72 hours. RESULTS: Of 539 infants, 79 (exposure) were matched with 158 infants (control). Infants born to mothers with PIH had lower birth weight, more likely to delivered through caesarean section and less likely to exposed to chorioamnionitis compared to infants born to mothers without PIH. No differences in RI were noted in infants with (median 1854; IQR 186, 13901) or without PIH (median 1359; IQR 210, 11302) (P-value 0.63). On conditional regression analysis, PIH did not predict RI (adjusted risk 1.15; 95% C.I 0.69–1.90; P value 0.594). No association between PIH and death (OR 3.14; 95% C.I 0.76–13.0; P-value 0.11) was identified. PIH was significantly associated with BPD on univariate analysis (odds ratio (OR) 2.29; 95% C.I 1.02–5.17; P-value 0.046), but on regression analysis was not significant (adjusted OR 1.26; 95% C.I 0.38–4.19; P-value 0.7) (Table 1 ). CONCLUSION: PIH was not associated with RI, mortality or BPD in this matched cohort. This contradicts from previous studies which may have been influenced with the survival bias. Further studies with larger samples are needed to confirm our results.